Response of Wheat to Different Irrigation Regimes Given under Poplar (populus Deltoides Bartr. Ex. Marsh) Based Agro forestry System - Singh, Avtar; Singh, R.P.; Kaur, Harinderjeet (Indian Forester, 2013)
A recently released, short duration wheat variety PBW-550, was intercropped in the poplar trees planted duringFebruary 2009 at a spacing of 5*4m on sandy soil at Punjab Agricultural University, Ludhiana. The experiment wasconducted using randomized block design with four irrigation treatments viz; I1 (Irrigation after 40mm CPE), I2 (Irrigation after 60mm CPE), I3 (Irrigation after 80mm CPE) and I4 (Irrigation after 100 mm CPE) given to poplar plantation and having six replications. The wheat yield was lower under the intercropping, more so during the second year, ascompared to the pure crop. The reduced irrigation regimes further reduced the grain yield of wheat and the best resultswere obtained with the I1 irrigation regime. The grain appearance score, test weight and grain hardness were all affected negatively during the second year of poplar growth and the restricted irrigation treatments. Consequently thegrain protein content increased with those treatments owing the shriveling of the kernels whereby the bran toendosperm ratio increases. However the effect on the sedimentation value was not so pronounced.